6+4r=5r

Simple and best practice solution for 6+4r=5r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+4r=5r equation:


Simplifying
6 + 4r = 5r

Solving
6 + 4r = 5r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-5r' to each side of the equation.
6 + 4r + -5r = 5r + -5r

Combine like terms: 4r + -5r = -1r
6 + -1r = 5r + -5r

Combine like terms: 5r + -5r = 0
6 + -1r = 0

Add '-6' to each side of the equation.
6 + -6 + -1r = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -1r = 0 + -6
-1r = 0 + -6

Combine like terms: 0 + -6 = -6
-1r = -6

Divide each side by '-1'.
r = 6

Simplifying
r = 6

See similar equations:

| 3-3*6-2=12 | | 18-r=-323 | | -15x-14= | | 4x-1=10x+8 | | 22+z=-180 | | Y=x+-5 | | 249=4x^2+32x-11 | | 8-d=d-6 | | 7+5j=6j | | Ax-y+z=6 | | -0.03x+0.11(x+16000)=2080 | | 5t+7r-15r= | | 3t-8=-2t+7 | | 18=3(v-13)-6 | | 5x+19+7x+98=213 | | 3t-8=-2the+7 | | 3t-8=-3 | | 5+4x=-1x | | 9h=-8+10h | | 8x-4=y | | 3(x+2)+23= | | 3x+7x-5x= | | 2(y-3)+5=3(x-1) | | 6(-5x+1)=-204 | | 0=1.5x-3.4 | | 2(710+1)= | | 3(-8+8x)=-192 | | (x-2)(x^2-2x+4)-x(x-3)(x+3)=26 | | 5q+-6q-p= | | 1410+2= | | 5(2t+3)=30-5t | | 0=9x^2+12x-3 |

Equations solver categories